Optimalisasi Layanan Bengkel Melalui Metode PDCA: Studi Kasus Peningkatan Efisiensi Super Cepat Service di PT ABC Sunter - Agung, Kurniawan; Rosalinda, Rosalinda; Wismantoro, Sindhu; Indriyati K, Retno; Hutasoit, Jisman (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
PT ABC, an official workshop leading in automotive service and repair, introduced the Super-Fast Service (SSC) service to meet the needs of customers who want regular maintenance of their vehicles quickly and reliably. However, the increasing demand for SSC services at PT ABC Sunter creates challenges in maintaining service quality and efficiency, as seen from the decline in Customer Satisfaction Index (CSI) scores in the